Your body beautiful : clockstopping secrets to staying healthy, strong, and sexy in your 30s, 40s, and beyond - Ashton, Jennifer (Avery, 2012)
"CBS Medical Correspondent Jennifer Ashton's smart, straight-talk guide to health for women that promises if you can commit to reinventing your health and wellness routines in your late 30s and 40s, you can feel younger, stronger and more vibrant than you did in your 20s"--